New financing mechanisms for the assignment (2013)
Funding of higher education in Colombia , has been debated in recent years by different sectors of society such as government, academia, students and even parents, due to increasing demand and insufficient supply of this service , showing results from a deficit of quotas by the public offering . This paper aims to analyze different financing alternatives made public university building on the existing allocation mechanisms and state employees. A review of literature, both nationally and internationally, seeking an approach to Colombia advances presented until 2011, according to the mechanisms implemented in other countries diversifying sources of funding mechanisms, such as joint funding and performance.